Ecological factors characteristics and distribution of Ganodermataceae family in the central highlands, Vietnam - Dai Nguyen, Nguyen Phuong; Thu, Do Huu; Dung, Le Ba (Academia Journal of Biology, 2013)
The ecological factors play a very important role on the growth and development of mushrooms.Therefore, understanding the correlational relationship between the ecological factors to the occurance of the mushroom species is essential. The fact that we carried out studying 4 major ecological factors such as temperature (to), humidity (m), height (h) and light intensity (l) affect the ocurrance (density) of Ganodermataceae species. It showed that these 4 factors have great impact to the presence (density) and distribution of the species represented by the following equation: F(x) = -2.648 + 0.040*sqrtl + 0.165986*m + 0.00153861*h - 0.138*t Presence frequency (density) is inversely proportional to the light intensity and temperature, proportional to the humidity and altitude above sea level, in the range studied. Based on the multivariate regression equation, the presence frequency (density) of the mushroom species can be predicted with ecological factors as a basis to allow for the detection of regional distribution of the species, as well as the principal for the cultivation and conservation of the species mentioned above.